Group theory and chemistry - Bishop, David M.; Bishop, David M. (New York, Dover Publications, 1973)
Concise, self-contained introduction to group theory and its application to chemical problems. Symmetry, symmetry operations, point groups, matrices, matrix representations, equivalent and reducible representations, irreducible representations and character tables, representations and quantum mechanics, molecular vibrations, molecular orbital theory, hybrid orbitals, and transition metal chemistry. Relevant math after each chapter. Advanced-undergraduate/graduate level. 1973 edition. Problems.
Appendix 279-288p.; Bibliography 289-296p.; Index 297-300p.
Keywords: Group theory; Chemistry